Analisis Dampak Kondisi Cuaca Ekstrem Terhadap Stabilitas Kinerja Jaringan Nirkabel - Axel Putra Alnis; Raja Akbar Sanjaini; Mahmudin Mahmudin (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Wireless networks have become an important part of modern communication infrastructure. However, their performance is often influenced by various environmental factors, including extreme weather conditions. This study aims to analyze the impact of various weather conditions such as heavy rain, high humidity, and extreme temperatures on the stability and quality of wireless networks. The method used is a quantitative approach with data collection of network performance under various weather conditions over a certain period of time. The parameters analyzed include latency, jitter, throughput, and packet loss rate. Initial results show that extreme weather, particularly heavy rain and high humidity, can lead to a significant decrease in network connection stability. These findings are expected to contribute to the planning and optimization of network systems, especially in areas with unpredictable climates.